2012
DOI: 10.1162/jocn_a_00162
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Visual- and Goal-related Neuronal Signals on the Trajectories of Saccadic Eye Movements

Abstract: Abstract■ During natural viewing, the trajectories of saccadic eye movements often deviate dramatically from a straight-line path between objects. In human studies, saccades have been shown to deviate toward or away from salient visual distractors depending on visual-and goal-related parameters, but the neurophysiological basis for this is not well understood. Some studies suggest that deviation toward is associated with competition between simultaneously active sites within the intermediate layers of the supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 42 publications
(80 reference statements)
7
68
0
Order By: Relevance
“…As we noted above, this paradigm reveals that more-salient distractors (i.e., those whose orientation contrasts more starkly with that of the surrounding lines) elicit greater deviations toward them, but only for short-latency saccades (van Zoest et al, 2012). This finding has been explained as the result of more-salient distractors eliciting more oculomotor activity during the planning of the saccade (White et al, 2012). However, this activity is transient, which results in salience effects on saccade trajectories disappearing at longer latencies (Donk & van Zoest, 2008).…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…As we noted above, this paradigm reveals that more-salient distractors (i.e., those whose orientation contrasts more starkly with that of the surrounding lines) elicit greater deviations toward them, but only for short-latency saccades (van Zoest et al, 2012). This finding has been explained as the result of more-salient distractors eliciting more oculomotor activity during the planning of the saccade (White et al, 2012). However, this activity is transient, which results in salience effects on saccade trajectories disappearing at longer latencies (Donk & van Zoest, 2008).…”
mentioning
confidence: 59%
“…A widely accepted explanation of saccade trajectory deviation is that it occurs because the visual system prepares eye movements to both the target and the distractor, and the resulting eye movement is an average or combination of the two different planned movements at the moment when the saccade is initiated (McPeek, Han, & Keller, 2003;McPeek & Keller, 2001;Port & Wurtz, 2003;Tipper, Howard, & Paul, 2001;White, Theeuwes, & Munoz, 2012). To the extent that the planned eye movement to the distractor has not been fully suppressed by the time the saccade is executed, the trajectory of the saccade will deviate toward the distractor.…”
mentioning
confidence: 99%
“…Key features of the 'SC' models accounting for saccadic inhibition also mirror properties of the FEF. Furthermore, recent neurophysiological evidence suggests that these cortical regions can also be a source of saccade curvature, since in a paradigm commonly used to elicit curvature, no curvature-related activity was detected in the SC throughout most of the delay period where it might have been expected (White et al, 2011). As already pointed out, if saccadic inhibition arises from multiple parts of the network, then Experiment 1 implies that OKN fast phases must be susceptible to all these loci, since the inhibition effect was actually larger not smaller than for saccades.…”
Section: Putative Role Of 'Higher-level' Processing In Fast-phasesmentioning
confidence: 99%
“…When an eye movement target is accompanied by a visual onset distractor, saccade trajectories typically deviate away from the distractor, so long as the distractor is relatively distal from the target (>about 30° polar angle; for a meta-analysis, see Wang and Theeuwes 2014). This observation has been attributed to unsuccessful suppression of neuronal activation evoked by the distractors (e.g., McPeek 2006; but see White et al 2012) and has been used as an index of spatial attention (see Van der Stigchel 2010, for a review). Furthering this line of research, Van Zoest et al (2012) recently demonstrated that more salient distractors induced stronger deviation in saccade trajectory than less salient ones.…”
Section: Introductionmentioning
confidence: 99%